Revisão do genero Oxyagrion Selys, 1876 (Odonata, Coenagrionidae) - Costa, Janira Martins (1977)
A revisionary study of the genus Oxyagrion Selys, 1876 offering an analysis of all scientific literature concerning it, listing of localities with geographical position (Brazilian map on the millionth) and altitude, reexamination of almost all existing types, subsequent designation of individual types, four keys of identification of eighteen species, one for females and three for males as follows: one based on penes, on anal appendages and another one combining colar and o ther other structural characters. Besides a minutious analysis of character of the genus, four new species and unknown females of five species are described and the remaining species are redescribed, most of them based on the types. Two species are not seen by the author, Ox. cardinale and Ox. bruchi. The male of Ox, cardinale, the females of Ox. bruchi and Ox. haematinum are unknown yet. Ox, divaricatum is presented as synonymous of Ox microstigma and Ox. terminale form b Ris, 1918 is provisionally traited as synonymous of Ox. bruchi. Affinities between oxyagrion and Acanthagrion are raised.